Sacri Canones Editandi: Studies on Medieval Canon Law in Memory of Jirí Kejr - Tanner, Norman (Asian Horizons, 2018)
Sacri Canones Editandi: Studies on Medieval Canon Law in Memory of Jirí Kejr, ed. Pavel Otmar Krafl, Ius canonicum medii aevi, vol. 1, Brno: Reprocentrum, 2017. Pages: 266. ISBN 9788027020980